Lab earthquakes reveal a wide range of rupture behaviors controlled by fault bends - Tom Gabrieli; Yuval Tal (Proceedings of the National Academy of Sciences, 2025)
Natural faults are typically nonplanar and exhibit multiple bends, which deviate from the general fault orientation at different angles. However, while such deviations are considered a key factor controlling earthquake propagation and, hence, its intensity and magnitude, direct experimental evidence of how bends affect earthquake ruptures is nearly nonexistent. Here, we present direct experimental observations of the interaction of dynamic frictional ruptures with fault (double-) bends of different angles. Using ultrahigh-speed photography, we capture highly detailed full-field images of the complex rupture dynamics that evolve as lab earthquakes in an analog material [poly(methylmethacrylate)] propagate through fault bends, as well as the resulting near-field ground motions. Releasing bends, which extend as the fault slips, intensify the rupture by promoting a transition to supershear propagation speeds (i.e., above the medium shear wave velocities) and a crack-like rupture style with spread-out slip, while restraining bends, which contract as the fault slips, slow or arrest the rupture. Surprisingly, we find that secondary back-propagating supershear ruptures are spontaneously triggered at intermediate-angle restraining bends. These constraints on the effect of natural fault geometry on the behavior and extent of earthquake ruptures have significant implications for earthquake source physics, seismic hazards, and the interpretation of seismic data.